Medical Ethics among Physicians and Nurses in Fayoum University Hospitals and Fayoum General Hsspital, Egypt - Heba H Rohym (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Medical ethics is a system that applies values to practice clinical medicine and in scientific research. This study aimed to assess knowledge and practice of medical ethics among physicians and nurses in Fayoum General Hospital and Fayoum University hospitals.Methods: A cross sectional descriptive study was carried out at Fayoum General Hospital and Fayoum University Hospital. The study was conducted from July2019to December 2019. Result: Our Study showed that there is statistically significant higher mean of ethics score among University hospital physicians and nurses than General hospital physicians and nurses. In each hospital physician show higher ethics score than nurses. There was no effect of gender on ethics score. There is statistically significant higher mean of ethics score among physician of surgical department more than medical departments. On the other hand there was no statistically significant difference in ethics score between different hospital departments in nurses in both study hospitals, also in each hospital and in each staff. Generally regardless type of hospital or staff there was statistically significant positive correlation between ethics score and age. Conclusion: Medical ethics learning courses must increase for physician and nurses especially for general hospitals.